Therapeutic role of neural stem cells in neurological diseases - Yang, Ling; Liu, Si-Cheng; Liu, Yi-Yi; Zhu, Fu-Qi; Xiong, Mei-Juan; Hu, Dong-Xia; Zhang, Wen-Jun (Frontiers in Bioengineering and Biotechnology, 2024)
The failure of endogenous repair is the main feature of neurological diseases that cannot recover the damaged tissue and the resulting dysfunction. Currently, the range of treatment options for neurological diseases is limited, and the approved drugs are used to treat neurological diseases, but the therapeutic effect is still not ideal. In recent years, different studies have revealed that neural stem cells (NSCs) have made exciting achievements in the treatment of neurological diseases. NSCs have the potential of self-renewal and differentiation, which shows great foreground as the replacement therapy of endogenous cells in neurological diseases, which broadens a new way of cell therapy. The biological functions of NSCs in the repair of nerve injury include neuroprotection, promoting axonal regeneration and remyelination, secretion of neurotrophic factors, immune regulation, and improve the inflammatory microenvironment of nerve injury. All these reveal that NSCs play an important role in improving the progression of neurological diseases. Therefore, it is of great significance to better understand the functional role of NSCs in the treatment of neurological diseases. In view of this, we comprehensively discussed the application and value of NSCs in neurological diseases as well as the existing problems and challenges.